Working in the Shadows for Transparency: Russ Hiebert, LabourWatch, Nanos Research, and the Making of Bill C-377 - Stevens, Andrew; Tucker, Sean (Labour / Le Travail, 2015)
Examines the controversy surrounding the passage of Bill C-377 by the Canadian federal parliament in 2012. Introduced as a private member's bill by Conservative MP Russ Hiebert in 2011, the legislation required unions to disclose publicly all of their activities to the Canada Revenue Agency under the Income Tax Act. The paper analyzes the anti-labour origins of the bill, which mirrored the union disclosure provisions of the US Taft-Hartley Act; it also considers the role of LabourWatch, the bill's principal private-sector Canadian advocate, as well as the Nanos Research polls commissioned by LabourWatch that appeared to show wide public support for the bill.